Intestinal Microbiota Participates in the Protective Effect of HO-1/BMMSCs on Liver Transplantation With Steatotic Liver Grafts in Rats - Yuan, Mengshu; Lin, Ling; Cao, Huan; Zheng, Weiping; Wu, Longlong; Zuo, Huaiwen; Tian, Xiaorong; Song, Hongli (Frontiers in Microbiology, 2022)
The present study aimed to explore whether heme oxygenase-1 (HO-1)-modified bone marrow mesenchymal stem cells (BMMSCs) have a protective effect on liver transplantation with steatotic liver grafts in rats, and to determine the role of the intestinal microbiota in such protection. HO-1/BMMSCs were obtained by transduction of Hmox1 gene (encoding heme oxygenase (HO-1))-encoding adenoviruses into primary rat BMMSCs. Steatotic livers were obtained by feeding rats a high-fat diet, and a model of liver transplantation with steatotic liver grafts was established. The recipients were treated with BMMSCs, HO-1/BMMSCs, or neither, via the portal vein. Two time points were used: postoperative day 1 (POD 1) and POD 7. The results showed that under the effect of HO-1/BMMSCs, the degree of steatosis in the liver grafts was significantly reduced, and the level of liver enzymes and the levels of pro-inflammatory cytokines in plasma were reduced. The effect of HO-1/BMMSCs was better than that of pure BMMSCs in the prolongation of the rats’ postoperative time. In addition, HO-1/BMMSCs promoted the recovery of recipients’ intestinal structure and function, especially on POD 7. The intestinal villi returned to normal, the expression of tight junction proteins was restored, and intestinal permeability was reduced on POD 7. The intestinal bacterial of the LT group showed significantly weakened energy metabolism and overgrowth. On POD 1, the abundance of Akkermansiaceae was higher. On POD 7, the abundance of Clostridiaceae increased, the level of lipopolysaccharide increased, the intestinal mucosal barrier function was destroyed, and the levels of several invasive bacteria increased. When treated with HO-1/BMMSCs, the energy metabolism of intestinal bacteria was enhanced, and on POD 1, levels bacteria that protect the intestinal mucosa, such as Desulfovibrionaceae, increased significantly. On POD 7, the changed intestinal microbiota improved lipid metabolism and increased the levels of butyrate-producing bacteria, such as Lachnospiraceae. In conclusion, HO1/BMMSCs have protective effects on steatotic liver grafts and the intestinal barrier function of the recipients. By improving lipid metabolism and increasing the abundance of butyrate-producing bacteria, the changed intestinal microbiota has a protective effect and prolongs the recipients’ survival time. urn:lsid:zoobank.org:pub:60C60DD0-23C5-447C-B797-B1D06EFD629A